2020
DOI: 10.3390/rs12172818
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Soil Moisture Downscaling in the Presence of Seasonal Difference

Abstract: The variation of soil moisture (SM) is a complex and synthetic process, which is impacted by numerous factors. The effects of these factors on soil moisture are dynamic. As a result, the relationship between soil moisture and explanatory variables varies with time and season. This kind of change should be considered in obtaining fine spatial resolution soil moisture products. We chose a study area with four distinct seasons in the temperate monsoon region. In this research, we established seasonal downscaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Random Forest (RF) served as our baseline machine learning algorithm, which has been used to down-scale soil moisture estimates in many studies e.g., [12,13,[24][25][26][27]. We also executed eXtreme Gradient Boosting (XGBoost) [12] and Gradient Boost (GBoost) [12].…”
Section: Machine Learning Implementationmentioning
confidence: 99%
“…Random Forest (RF) served as our baseline machine learning algorithm, which has been used to down-scale soil moisture estimates in many studies e.g., [12,13,[24][25][26][27]. We also executed eXtreme Gradient Boosting (XGBoost) [12] and Gradient Boost (GBoost) [12].…”
Section: Machine Learning Implementationmentioning
confidence: 99%
“…They found that XGBoost was selected most frequently and had the highest accuracy, followed by RF. Similarly, Yan et al [16] compared three ML algorithms: RF, SVR, and k-nearest neighbors (KNN) for AMSR-E and AMSR2 products. They found that RF had the best accuracy and used it to establish seasonal downscaling models.…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1980s, when the Scanning Multichannel Microwave Radiometer, carried by Nimbus‐8, began providing SM products, there have been developments to improve the spatial and temporal accuracy and resolution of products (Fan et al., 2022). As such, the market presents numerous remote sensing‐based SM projects retrieved from various satellites using various algorithms, for example, the Soil Moisture and Ocean Salinity of the European Space Agency with a spatial resolution of 35–50 km (Xiao et al., 2017), the Soil Moisture Active and Passive of the National Aeronautics and Space Administration with a spatial resolution of 36 km (Fan et al., 2022), and the Advanced Microwave Scanning Radiometer–Earth Observing System (AMSR‐E/2), of Japan Aerospace Exploration Agency's; with a spatial resolution of 25 km (Yan & Bai, 2020). The challenge with these SM products is their coarse spatial resolution; hence, an alternative method to estimate SM at a local scale is required.…”
Section: Introductionmentioning
confidence: 99%